Where did all this pi come from?

Calculus Level 5

n = 1 ζ ( 3 n ) 1 n = ln ( A π ) + π cos ( π B ) ln ( e π C + tan ( π D ) ) \sum_{n=1}^{\infty} \dfrac{\zeta(3n) - 1}{n} = \ln(A \pi) + \pi \cos\left(\dfrac{\pi}{B}\right) - \ln\left(e^{\pi \sqrt{C}} + \tan\left(\dfrac{\pi}{D}\right)\right)

In the above equation, A , B , C , D A,B,C,D are natural numbers. Find the value of A + B + C + D A+B+C+D .

Notation: ζ ( ) \zeta(\cdot) denotes the Riemann Zeta function .


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Dec 21, 2016

n = 1 ζ ( 3 n ) 1 n = n = 1 1 n k = 2 1 k 3 n = k = 2 n = 1 1 n k 3 n = k = 2 ln ( 1 k 3 ) = ln ( k = 2 ( 1 k 3 ) ) = ln ( cosh 1 2 π 3 3 π ) = ln ( e π 3 + 1 6 π e 1 2 π 3 ) = ln ( 6 π ) + 1 2 π 3 ln ( e π 3 + 1 ) = ln ( 6 π ) + π cos 1 6 π ln ( e π 3 + tan 1 4 π ) \begin{aligned} \sum_{n=1}^\infty \frac{\zeta(3n)-1}{n} & = \sum_{n=1}^\infty \frac{1}{n}\sum_{k=2}^\infty \frac{1}{k^{3n}} \; = \; \sum_{k=2}^\infty \sum_{n=1}^\infty \frac{1}{n\,k^{3n}} \\ & = -\sum_{k=2}^\infty \ln\big(1 - k^{-3}\big) \; = \; -\ln\left(\prod_{k=2}^\infty \big(1 - k^{-3}\big)\right) \\ & = -\ln\left(\frac{\cosh \frac12\pi\sqrt{3}}{3\pi}\right) \; =\; -\ln\left(\frac{e^{\pi\sqrt{3}} + 1}{6\pi e^{\frac12\pi \sqrt{3}}}\right) \\ & = \ln(6\pi) + \tfrac12\pi\sqrt{3} - \ln\big(e^{\pi\sqrt{3}} + 1\big) \; = \; \ln(6\pi) + \pi\cos\tfrac16\pi - \ln\big(e^{\pi\sqrt{3}} + \tan\tfrac14\pi\big) \end{aligned} making the answer 6 + 6 + 3 + 4 = 19 6 + 6 + 3 + 4 = \boxed{19} .

How do you know that k = 2 ( 1 k 3 ) = cosh ( π 3 2 ) 3 π \displaystyle\prod_{k=2}^{\infty} (1-k^{-3}) = \dfrac{\cosh\left(\dfrac{\pi \sqrt{3}}{2}\right)}{3\pi} ?

Ariel Gershon - 4 years, 5 months ago

Log in to reply

It's a standard formula.

Mark Hennings - 4 years, 5 months ago

Try deriving this: k = 2 ( 1 z n k n ) = k = 0 n 1 1 Γ ( 1 z exp [ ( 2 π k i / n ) ] ) \prod_{k=2}^{\infty} \left ( 1- \frac{z^n}{k^n} \right )= \prod_{k=0}^{n-1} \frac{1}{\Gamma \left ( 1-z\exp \left [ \left ( 2\pi k i /n \right ) \right ] \right )} It is useful here.

Aditya Kumar - 4 years, 4 months ago
Ariel Gershon
Dec 22, 2016

Let H ( x ) H(x) be the harmonic function, which has the following Taylor series: H ( x ) = k = 2 ζ ( k ) ( x ) k 1 x H ( x ) = k = 2 ζ ( k ) x k \begin{aligned} H(x) & = -\sum_{k=2}^{\infty} \zeta(k)(-x)^{k-1} \\ -x H(-x) & = \sum_{k=2}^{\infty} \zeta(k)x^k \\ \end{aligned} Let w = 1 + 3 2 w = \dfrac{-1+\sqrt{-3}}{2} . Then 1 + w + w 2 = 0 1+w+w^2 = 0 . Therefore, x H ( x ) w x H ( w x ) w 2 x H ( w 2 x ) = k = 2 ( ζ ( k ) x k + ζ ( k ) ( w x ) k + ζ ( k ) ( w 2 x ) k ) x H ( x ) w x H ( w x ) w 2 x H ( w 2 x ) = 3 n = 1 ζ ( 3 n ) x 3 n x H ( x ) w x H ( w x ) w 2 x H ( w 2 x ) 3 x 3 1 x 3 = 3 n = 1 ( ζ ( 3 n ) 1 ) x 3 n H ( x ) w H ( w x ) w 2 H ( w 2 x ) 3 x 2 1 x 3 = n = 1 3 ( ζ ( 3 n ) 1 ) x 3 n 1 \begin{aligned} -x H(-x) -wx H(-wx) - w^2x H(-w^2x) & = \sum_{k=2}^{\infty} \left(\zeta(k)x^k+\zeta(k)(wx)^k+\zeta(k)(w^2x)^k\right) \\ -x H(-x) -wx H(-wx) - w^2x H(-w^2x) & = 3\sum_{n=1}^{\infty} \zeta(3n)x^{3n} \\ -x H(-x) -wx H(-wx) - w^2x H(-w^2x) - \dfrac{3x^3}{1-x^3} & = 3\sum_{n=1}^{\infty} \left(\zeta(3n)-1\right)x^{3n} \\ -H(-x) -w H(-wx) - w^2 H(-w^2x) - \dfrac{3x^2}{1-x^3} & = \sum_{n=1}^{\infty} 3\left(\zeta(3n)-1\right)x^{3n-1} \end{aligned}

Integrating both sides gives us:

ln ( x ) ! γ x + ln ( w x ) ! γ w x + ln ( w 2 x ) ! γ w 2 x + ln ( 1 x 3 ) = n = 1 ( ζ ( 3 n ) 1 ) x 3 n n ln ( 1 x ) ! + ln ( 1 w x ) ! + ln ( 1 w 2 x ) ! = n = 1 ( ζ ( 3 n ) 1 ) x 3 n n \begin{aligned} \ln (-x)! - \gamma x + \ln(-wx)! - \gamma wx + \ln(-w^2x)! - \gamma w^2x + \ln(1-x^3) & = \sum_{n=1}^{\infty} \dfrac{\left(\zeta(3n)-1\right)x^{3n}}{n} \\ \ln (1-x)! + \ln(1-wx)! + \ln(1-w^2x)! & = \sum_{n=1}^{\infty} \dfrac{\left(\zeta(3n)-1\right)x^{3n}}{n} \end{aligned}

Now substitute x = 1 x = 1 :

n = 1 ζ ( 3 n ) 1 n = ln ( ( 1 w ) ! ( 1 w 2 ) ! ) = ln ( ( 3 + 3 2 ) ! ( 3 3 2 ) ! ) = ln ( 3 + 3 2 1 + 3 2 3 3 2 1 3 2 ) + ln ( ( 1 + 3 2 ) ! ( 1 3 2 ) ! ) \begin{aligned} \sum_{n=1}^{\infty} \dfrac{\zeta(3n)-1}{n} & = \ln\left((1-w)! (1-w^2)!\right) \\ & = \ln\left(\left(\dfrac{3+\sqrt{-3}}{2}\right)! \left(\dfrac{3-\sqrt{-3}}{2}\right)! \right) \\ & = \ln\left(\dfrac{3+\sqrt{-3}}{2} * \dfrac{1+\sqrt{-3}}{2} * \dfrac{3-\sqrt{-3}}{2} * \dfrac{1-\sqrt{-3}}{2}\right) + \ln\left(\left(\dfrac{-1+\sqrt{-3}}{2}\right)! \left(\dfrac{-1-\sqrt{-3}}{2}\right)! \right) \end{aligned}

Now we can use Gauss' theorem which says that ( x 1 ) ! ( x ) ! = π csc ( π x ) (x-1)!(-x)! = \pi \csc(\pi x) :

n = 1 ζ ( 3 n ) 1 n = ln ( 3 ) + ln ( π csc ( π ( 1 + 3 2 ) ) ) = ln ( 3 π ) ln ( cos ( π 3 2 ) ) = ln ( 3 π ) ln ( cosh ( π 3 2 ) ) = ln ( 3 π ) ln ( e π 3 + 1 2 e 3 π / 2 ) = ln ( 6 π ) + 3 2 π ln ( e π 3 + 1 ) n = 1 ζ ( 3 n ) 1 n = ln ( 6 π ) + π cos ( π 6 ) ln ( e π 3 + tan ( π 4 ) ) \begin{aligned} \sum_{n=1}^{\infty} \dfrac{\zeta(3n)-1}{n} & = \ln(3) +\ln\left(\pi \csc\left(\pi\left(\dfrac{1+\sqrt{-3}}{2}\right)\right) \right) \\ & = \ln(3\pi) - \ln\left(\cos\left(\dfrac{\pi\sqrt{-3}}{2} \right)\right) \\ & = \ln(3\pi) - \ln\left(\cosh\left(\dfrac{\pi\sqrt{3}}{2} \right)\right) \\ & = \ln(3\pi) - \ln\left(\dfrac{e^{\pi\sqrt{3}}+1}{2e^{\sqrt{3}\pi/2}}\right) \\ & = \ln(6\pi) + \dfrac{\sqrt{3}}{2}\pi - \ln(e^{\pi\sqrt{3}}+1) \\ \sum_{n=1}^{\infty} \dfrac{\zeta(3n)-1}{n} & = \ln(6\pi) + \pi \cos\left(\dfrac{\pi}{6}\right) - \ln\left(e^{\pi\sqrt{3}}+\tan\left(\dfrac{\pi}{4}\right)\right) \end{aligned}

Aareyan Manzoor
Jul 7, 2017

notice that n = 1 ζ ( a n ) 1 n = n = 1 k = 2 1 n k a n = k = 2 ln ( 1 k a ) = k = 2 ln ( n = 1 a ( 1 ω n k 1 ) ) = ln ( k = 2 n = 1 a ( 1 ω n k 1 ) ) \sum_{n=1}^\infty \dfrac{\zeta(an)-1}{n}=\sum_{n=1}^\infty \sum_{k=2}^\infty \dfrac{1}{nk^{an}}=-\sum_{k=2}^\infty \ln(1-k^{-a})=\\-\sum_{k=2}^\infty \ln(\prod_{n=1}^a(1-\omega^n k^{-1}))=-\ln\left(\prod_{k=2}^\infty\prod_{n=1}^a(1-\omega^n k^{-1})\right) where ω \omega is an a t h a^{th} primitive root of unity. using wiestrass product 1 Γ ( z ) = z ( 1 + z ) e γ z k = 2 e z / k ( 1 + z k 1 ) 1 Γ ( z + 2 ) = e γ z k = 2 e z / k ( 1 + z k 1 ) \dfrac{1}{\Gamma(z)}=z(1+z) e^{\gamma z} \prod_{k=2}^\infty e^{-z/k} (1+zk^{-1})\to\dfrac{1}{\Gamma(z+2)}=e^{\gamma z} \prod_{k=2}^\infty e^{-z/k} (1+zk^{-1}) plugging in z = ω , ω 2 . . . ω a 1 , z=-\omega,-\omega^2...-\omega^{a-1}, into the first one and z = 1 z=-1 in the second one and multiplying n = 1 a 1 1 Γ ( ω n ) = ( n = 1 a 1 ω n ( 1 ω n ) e γ ω n ( k = 2 e ω n / k ( 1 ω n k 1 ) ) ) ( e γ k = 2 e 1 / k ( 1 k 1 ) ) \prod_{n=1}^{a-1} \dfrac{1}{\Gamma(-\omega^n)}=\left(\prod_{n=1}^{a-1} -\omega^n(1-\omega^n) e^{\gamma \omega^n} \left(\prod_{k=2}^\infty e^{-\omega^n/k} (1-\omega^n k^{-1})\right)\right)\left(e^{-\gamma } \prod_{k=2}^\infty e^{1/k} (1-k^{-1})\right) by using properties of roots of unity the product ends up being, namely their sums been 0 and product been ( 1 ) a 1 (-1)^{a-1} , n = 1 a 1 1 Γ ( ω n ) = a n = 1 a k = 2 ( 1 ω n k 1 ) \prod_{n=1}^{a-1} \dfrac{1}{\Gamma(-\omega^n)}=a\prod_{n=1}^a\prod_{k=2}^\infty (1-\omega^n k^{-1}) we can manipulate this into ln ( n = 1 a k = 2 ( 1 ω n k 1 ) ) = ln ( a ) + n = 1 a 1 ln ( Γ ( ω n ) ) n = 1 ζ ( a n ) 1 n = ln ( a ) + n = 1 a 1 ln ( Γ ( ω n ) ) -\ln\left(\prod_{n=1}^a\prod_{k=2}^\infty (1-\omega^n k^{-1})\right)=\ln(a)+\sum_{n=1}^{a-1} \ln(\Gamma(-\omega^n))\to\sum_{n=1}^\infty \dfrac{\zeta(an)-1}{n}=\ln(a)+\sum_{n=1}^{a-1} \ln(\Gamma(-\omega^n)) the rest is just easy plugging a = 3 a=3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...